2018
DOI: 10.1161/circep.118.006408
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Delivery of Hydrogel-Encapsulated Amiodarone to the Epicardium Reduces Atrial Fibrillation

Abstract: The pericardium is an underutilized therapeutic site and may be a new treatment strategy for AF and other cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…71 Multiple studies have shown that epicardial spraying of drug-loaded hydrogels is well tolerated, increases drug effectiveness over other administrative routes, and reduces the risk of extracardiac adverse drug side effects. 36,72,73 Another clinical study of 100 patients undergoing coronary artery bypass grafting showed that diffuse epicardial spraying of the drug amiodarone loaded in a polyethylene glycol-based hydrogel reduced postoperative atrial fibrillation for a period of 14 days. 35 Demonstrated therapeutic potential.…”
Section: Ipdmentioning
confidence: 99%
“…71 Multiple studies have shown that epicardial spraying of drug-loaded hydrogels is well tolerated, increases drug effectiveness over other administrative routes, and reduces the risk of extracardiac adverse drug side effects. 36,72,73 Another clinical study of 100 patients undergoing coronary artery bypass grafting showed that diffuse epicardial spraying of the drug amiodarone loaded in a polyethylene glycol-based hydrogel reduced postoperative atrial fibrillation for a period of 14 days. 35 Demonstrated therapeutic potential.…”
Section: Ipdmentioning
confidence: 99%
“…The amiodarone loaded PEG hydrogel showed a success in a porcine model of atrial fibrillation by reducing the duration of atrial fibrillation compared with delivery of gel alone. Furthermore, off target amiodarone levels were significantly reduced in comparison with systemic delivery after 28 days (126,127). A recent study by Whyte et al has shown promising results for a refillable cardiac reservoir that can AUTHOR ACCEPTED MANUSCRIPT © Controlled Release Society 26 be placed on the epicardium in a minimally invasive fashion using a mini-thoracotomy for the delivery of stem cells to the heart post myocardial infarction.…”
Section: Delivery Of Cardioprotectants To the Heartmentioning
confidence: 99%
“…They demonstrated that pericardium hydrogels can deliver therapeutics directly to the heart enabling a continued release of drug for several weeks and reducing off-target organ accumulations [135] . These results highlight the possibility to use pericardium as an alternative therapeutic site for treatment strategy for AF and other cardiovascular diseases.…”
Section: Hydrogelsmentioning
confidence: 99%